Association between soybean product consumption and executive function in Chinese Tibetan children and adolescents - Yin, Xiaojian; Zhang, Feng; Bi, Cunjian; Liu, Yuan; Guo, Yaru; Sun, Pengwei; Hong, Jun (Frontiers in Nutrition, 2024)
Objective: This sought to explore the association between soybean product consumption and executive function (EF) in Chinese Tibetan adolescents in high-altitude areas. Methods: A total of 1,184 Tibetan children and adolescents were tested on demographic variables, soybean product consumption, and executive function in Lhasa and Nagchu regions of Tibet, China, using stratified whole population sampling. One-way ANOVA, linear regression analysis, and logistic regression analysis were used to analyze the associations existing between soybean product consumption and executive function. Results: The proportions of Hardly ever, Occasionally, and Often in Soy Consumption among Tibetan children and adolescents in high altitude areas of Tibet, China were 21.7%, 50.3%, and 28.0%, respectively. The difference in 2 back reaction time among Tibetan children and adolescents with different soybean product consumption was statistically significant (F= 6.374, P=0.002).The difference in conversion function reaction time was also statistically significant (F= 8.129, P<0.001). Taking the soybean product consumption ≥6 t/w group as the reference group, after adjusting the relevant factors, those with soybean product consumption ≤1 t/w showed a statistically significant increase in Inhibit Function Dysfunction (OR=1.844, 95% CI: 1.152,2.951) and Conversion Function Dysfunction (OR=2.008, 95% CI: 1.106,3.646) had an increased risk of Conversion Function Dysfunction (OR=2.008, 95% CI: 1.106,3.646), which was significantly different (P<0.05). Conclusions: There is an association between soybean product consumption and inhibitory control and translational flexibility of brain executive functions in Chinese Tibetan children and children and adolescents at high altitude.